1995
DOI: 10.1111/j.1600-0420.1995.tb00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for diabetic retinopathy

Abstract: A screening program for diabetic eye disease was established in Iceland in 1980. Diabetics involved in the screening program have a low prevalence of blindness, 1% in type 1 and 1.6% in type 2. We examined ways to make the screening program more efficient by identifying subgroups at low risk of developing eye disease that require treatment and therefore need less frequent screening. We studied whether diabetic eye disease screening programs may be trimmed by excluding children and examining diabetics without r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 29 publications
0
37
1
Order By: Relevance
“…This study can be seen as an extension of our earlier studies [10,11], which show that alternate year screening for diabetic eye disease seems to be safe and effective in diabetic patients without retinopathy and, by doing this, the financial savings are substantial. In this study we have gone further and used information technology and available epidemiological studies to standardise the risk and make individual determinations of screening intervals for diabetic eye disease.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This study can be seen as an extension of our earlier studies [10,11], which show that alternate year screening for diabetic eye disease seems to be safe and effective in diabetic patients without retinopathy and, by doing this, the financial savings are substantial. In this study we have gone further and used information technology and available epidemiological studies to standardise the risk and make individual determinations of screening intervals for diabetic eye disease.…”
Section: Discussionmentioning
confidence: 58%
“…In 1993, Kalm and Jonsson [9] proposed variable screening intervals based on risk margins and in 1994 the Icelandic screening programme moved in this direction by lengthening the screening interval to 2 years for diabetic patients without retinopathy [10]. This approach has proven to be safe and effective [11], and has been adopted by many diabetic eyescreening programmes.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous report on the same group, we found a 2-year incidence of any retinopathy of 23% (Kristinsson et al 1995). Our 4-year incidence of any retinopathy is significantly lower than in the Wisconsin 4-year incidence study (Klein et al 1989a), where the incidence of any retinopathy in type 1 diabetics was 59.0% (160 out of 271) ( Table 3).…”
Section: Retinopathymentioning
confidence: 77%
“…A review of the first 10 years of diabetic screening in Iceland between 1980 and 1990 revealed that no patient had progressed from no retinopathy to sight-threatening retinopathy in less than 2 years 6. We concluded, and reported, that it was adequate to examine patients with diabetes without retinopathy every other year and immediately introduced this routine into our screening system.…”
mentioning
confidence: 86%